2015
DOI: 10.4238/2015.november.18.44
|View full text |Cite
|
Sign up to set email alerts
|

Biological changes of Enterococcus faecalis in the viable but nonculturable state

Abstract: ABSTRACT. Enterococcus faecalis may enter a viable but nonculturable (VBNC) state under adverse conditions. E. faecalis, the major bacterial species present in failed root canal treatments, is thought to survive after endodontic treatment by entering a VBNC state. In this study, we characterized the VBNC state of E. faecalis. We designed 3 different protocols to successfully induce the VBNC state. Approximately one-third of bacteria entered a VBNC state after 15-30 days, and all remained viable for at least 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The entry of bacteria into a state described as VBNC has been reported repeatedly for a large number of bacterial species, and among them several Gram-positive bacteria, including bacteria that reside in the oral cavity (Hiyari and Bennett, 2011; E et al, 2015). A bacterium in the VBNC state has been defined as a cell which can be demonstrated to be metabolically active, while being incapable of undergoing the sustained cellular division required for growth in or on a medium normally supporting growth of that cell (Koch, 1997).…”
Section: Discussionmentioning
confidence: 92%
“…The entry of bacteria into a state described as VBNC has been reported repeatedly for a large number of bacterial species, and among them several Gram-positive bacteria, including bacteria that reside in the oral cavity (Hiyari and Bennett, 2011; E et al, 2015). A bacterium in the VBNC state has been defined as a cell which can be demonstrated to be metabolically active, while being incapable of undergoing the sustained cellular division required for growth in or on a medium normally supporting growth of that cell (Koch, 1997).…”
Section: Discussionmentioning
confidence: 92%
“…The possible explanation may be that E. faecalis can adapt into a viable, but nonculturable (VBNC), state when exposed to some environmental stresses, and can be resuscitated later in a suitable environment ( 24 ). Previous studies indicated that E. faecalis entered a VBNC state within 2 weeks and remained viable for at least 2 months ( 25 , 26 ). When entering the VBNC state, the E. faecalis shape changed from coccoid to irregular, and it lost its ability to break down lactose, D-mannitol and D-sorbitol ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…When entering the VBNC state, the E. faecalis shape changed from coccoid to irregular, and it lost its ability to break down lactose, D-mannitol and D-sorbitol ( 24 ). Furthermore, the cells can still attach to dentine and Type I collagen fibres, but cannot penetrate the dentinal tubules ( 25 ). These situations might lower the pathogenicity of the bacteria; however, the resuscitated cells can initiate infection after recovery.…”
Section: Discussionmentioning
confidence: 99%